Serum Sickness after Equine Rabies Immunoglobulin in Identical Male Twins: Two Case Reports - Weeratian Tawanwongsri (2020)
© 2019 The Author(s). We, hereby, report two cases of serum sickness in adult male identical twins who had received equine rabies immunoglobulin as a postexposure rabies treatment after cat scratches. The younger brother developed low-grade fever, polyarthritis, and multiple erythematous maculopapular eruptions, whereas low-grade fever and urticaria-like eruptions were detected in the elder brother. Both patients received a 7-day course of low-dose prednisolone and achieved good responses without recurrent attacks.